ANXIETY AND DEFENSE MECHANISM OF THE MAIN CHARACTER IN BRIAN PINKNEYâ€™S â€œJOJOâ€™S FLYING SIDE KICKâ€ PICTURE BOOK (PANOPTICON: Journal of English Studies, 2022)
This thesis is titled "Anxiety and Defense Mechanism of The Main Character in Brian Pinkney's Jojoâ€™s Flying Side kick Picture Book". The purpose of this study is to analyze how the anxiety experienced by the main character in Jojoâ€™s Flying Sidekick picture book can influence her subconscious mind to bring up new perceptions about something. In addition, the writer also analyzed the defense mechanism used by the main character in dealing with her anxiety problem by referring to the psychological approach developed by Sigmund Freud. In conducting this research, the writer used the qualitative approach method where the writer uses pictures, dialogues, perspectives, and thoughts contained in the research object as data or analysis foundation. The results showed that in overcoming the anxiety problem, the main character in Jojoâ€™s Flying Sidekick used more than one defense mechanism. Those are regression, intellectualization, and displacement. Keywords: Anxiety, Defense mechanism.